Src Family Kinases Inhibition Ameliorates Hypoxic-Ischemic Brain Injury in Immature Rats - Qiu, Han; Qian, Tianyang; Wu, Tong; Gao, Ting; Xing, Qinghe; Wang, Laishuan (Frontiers in Cellular Neuroscience, 2021)
Hypoxic-ischemic (HI) injury is one of the initial factors contributing to neonatal brain injury. Src family kinases (SFKs) are considered to act as molecular hubs for N-methyl-d-aspartate receptor (NMDAR) regulation and participate in the HI injury process. The objectives of this study were to evaluate the levels of phospho-Src (p-Src), the relationship between NMDARs and SFKs, and the effects of SFK inhibition on an immature rat HI brain injury model. The model was induced in 3-day-old Sprague–Dawley rats using the Rice-Vannucci model operation. The level of p-Src was evaluated using Western blotting. The association of NMDARs with SFKs was detected using Western blotting and coimmunoprecipitation. After intraperitoneal injection of 4-amino-5-(4-chlorophenyl)-7-(t-butyl) pyrazolo [3,4-d] pyrimidine (PP2), an SFK-selective inhibitor, neuropathological changes were observed by performing H&E and immunofluorescence staining, and the neurological functions were assessed using the following behavioral tests: modified neurological severity score, open field test, and Morris water maze test. The levels of p-Src first decreased at 0 h after injury, increased at 2 h after injury, and continuously decreased from 6 h to 3 days. Along with the increased p-Src levels observed at 2 h after injury, the phosphorylation of NMDAR subunit NR2B at tyrosine 1472 was increased. Following the administration of PP2, the increased p-Src and NMDAR-2B levels detected at 2 h after injury were decreased, and tissue injury and myelin basic protein expression were improved at 7 days after injury. The PP2 intervention improved the performance of injured rats on behavioral tests. In conclusion, we determined the patterns of p-Src expression after HI brain injury in immature rats and showed a relationship with the activated NMDA receptor. The inhibition of p-Src ameliorates neuropathological changes and damages neurological functions induced by HI injury.